The role of associative learning in healthy and sustainable food evaluations: An event-related potential study. (October 2022) - Chen, Pin-Jane; Coricelli, Carol; Kaya, Sinem; Rumiati, Raffaella Ida; Foroni, Francesco
Abstract: Individuals in industrialized societies frequently include processed foods in their diet. However, overconsumption of heavily processed foods leads to imbalanced calorie intakes as well as negative health consequences and environmental impacts. In the present study, normal-weight healthy individuals were recruited in order to test whether associative learning ( Evaluative Conditioning, EC) could strengthen the association between food-types ( minimally processed and heavily processed foods) and concepts (e.g., healthiness ), and whether these changes would be reflected at the implicit associations, at the explicit ratings and in behavioral choices. A Semantic Congruency task (SC) during electroencephalography recordings was used to examine the neural signature of newly acquired associations between foods and concepts. The accuracy after EC towards minimally processed food (MP-food) in the SC task significantly increased, indicating strengthened associations between MP-food and the concept of healthiness through EC. At the neural level, a more negative amplitude of the N400 waveform, which reflects semantic incongruency, was shown in response to MP-foods paired with the concept of unhealthiness in proximity of the dorsal lateral prefrontal cortex (DLPFC). This implied the possible role of the left DLPFC in changing food representations by integrating stimuli's features with existing food-relevant information. Finally, the N400 effect was modulated by individuals' attentional impulsivity as well as restrained eating behavior. Highlights: Evaluative conditioning strengthens implicit and explicit food associations. Stronger food associations after conditioning are underpinned by greater N400. Left DLPFC seems to integrate new information into food semantic representations. Individuals with higher attentional impulsivity show greater changes of N400 effect.